Research on the Impact of Social Propaganda and Guidance Policies on Public Green Travel Intention: Evidence From China - Yang, Dafei; Sun, Shouheng (Frontiers in Sustainability, 2022)
Social propaganda and guidance policies have important practical significance for promoting public green travel. In recent years, the rapid development of digital technology, network, and mobile communication technology has promoted a revolutionary change in the dissemination of information and services. However, in the era of new media communication driven by emerging technologies, there is still a lack of research on the impact of social propaganda and guidance policies on public willingness to travel green. Based on the theory of planned behavior and the survey research of China's urban residents, this study investigates the impact of social propaganda and guidance policies on public willingness to travel green. Regression analysis is used to identify the influencing factors of public green travel willingness, and to reveal the internal impact mechanism of social propaganda and guidance policies on public green travel willingness. The mediating role of public green travel attitude, subjective norm, and perceived behavior control in social propaganda and guidance policy and travel willingness are also empirically analyzed. The results show that social propaganda and guidance policies have a significant positive impact on green travel attitudes, subjective norms, perceived behavior control, and green travel intentions. Green travel attitude, subjective norm, and perceived behavior control play a mediating role in the relationship between social propaganda and guiding policies and green travel willingness, but the mediating effect of the subjective norm is relatively weak.